Conflict Management and Employee Performance in Manafwa District Local Government, Uganda - Abigail Oba (Uganda Christian University, 2024)
This study investigated the influence of conflict management on employee performance in Manafwa district local government. The study specifically examined the influence of Arbitration, Negotiation and confrontation on employee performance in Manafwa District Local Government. The study used a cross section survey research design with both qualitative and quantitative approaches. The study population involved the Chief Administrative Officer, Heads of Departments, Principle personnel officer, Town clerks, sub-county chiefs and community development officers. Data collection utilized questionnaires and interviews. Data was analysed to obtain frequencies, mean, standard deviation, correlations and regression statistics to ascertain the significance of the variables. It was revealed that Arbitration has a significant influence on employee performance (r=.649, p=.000). Respondents appreciated that whenever arbitration is applied in managing conflicts, employees performance is improved. In addition, it was discovered that Negotiation influences employee performance (r=.555, p=.000). Respondents revealed that whenever there is a conflict, the parties in dispute are given an opportunity to meet, discuss and agree amicably. Respondents believe that after negotiation, there is improved employee relations that stimulates employees productivity. The study also realized that confrontation slightly influences employee performance (r=.254, p=.043). Respondents revealed that confrontation can only influence employee performance if it is done well. In conclusion, Conflict management positively influences employee performance in Manafwa District Local Government. It was therefore recommended that Arbitration committees should maintain high level of integrity, transparency and impartiality, negotiation should also be applied in other situations even if there is no conflict and Confrontation can be used only in situations of low productivity, delay in accomplishment of tasks and absenteeism of employees at work.